Peduli Kesehatan Jiwa Lansia Melalui Latihan “Asitifrop” (Affirmasi Positif dan Relaksasi Otot Progresif) Dan Eteksidini Kesehatan Mental Lansia Di Desa Jemundo - Aristina Halawa; Ethica Sari; NadyaAmbarwati; Ni Putu Widari (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2025)
According to the World Health Organization (WHO), the global prevalence of mental disorders in the elderly is 61.6%. 2018 Balitbangkes data shows that there are 4 major health problems experienced by the elderly, namely hypertension, diabetes mellitus (DM), stroke and emotional mental disorders. Mental health disorders that often occur in the elderly are depression, anxiety and dementia. The aim of this community service is to increase the elderly's knowledge about mental health, prevent mental health problems by carrying out positive affirmations and progressive muscle relaxation and cadres can carry out early detection of mental health problems in the elderly. The methods used in this community service are counseling about mental health for the elderly, "ASITIF-ROP" training conducted for 50 elderly people and training on Early Detection of Mental Health in the Elderly and for 20 cadres. The result of this activity is that elderly knowledge about elderly mental health has increased. Most of the elderly's knowledge level is at a good level of knowledge, namely 36 elderly (72%) whereas previously only 6 elderly (12%) were at a good level. The elderly's ability to perform ASITIFROP and early detection is 100% complete after training. The stress level of the elderly also decreased, where previously 23 (46%) experienced mild stress and 27 (54%) experienced moderate stress, but after doing the ASTIFROP exercise, the majority of elderly experienced mild stress, 46 (92%). All participants were very enthusiastic about participating in the activity as shown by the many questions asked and the positive responses of the elderly during the discussion. It is hoped that similar activities can be continued regularly and maintained as a means of health education for the elderly.